Challenges With Controlling Varicella in Prison Settings: Experience of California, 2010 to 2011. (October 2014) - Leung, Jessica; Lopez, Adriana S.; Tootell, Elena; Baumrind, Nikki; Mohle-Boetani, Janet; Leistikow, Bruce; Harriman, Kathleen H.; Preas, Christopher P.; Cosentino, Giorgio; Bialek, Stephanie R.; Marin, Mona
This article describes the epidemiology of varicella in one state prison in California during 2010 and 2011, control measures implemented, and associated costs. Eleven varicella cases were reported, of which nine were associated with two outbreaks. One outbreak consisted of three cases and the second consisted of six cases with two generations of spread. Among exposed inmates serologically tested, 98% (643/656) were varicella-zoster virus seropositive. The outbreaks resulted in > 1, 000 inmates exposed, 444 staff exposures, and > $160, 000 in costs. The authors documented the challenges and costs associated with controlling and managing varicella in a prison setting. A screening policy for evidence of varicella immunity for incoming inmates and staff and vaccination of susceptible persons has the potential to mitigate the impact of future outbreaks and reduce resources necessary to manage cases and outbreaks.